Desabafa aí - comunidade de apoio ao público LGBT - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This work addresses the need for a specific social network for minorities, focusing on assistance and support, filling a gap in the market. The introduction emphasizes the importance of an inclusive platform, free from hate speech and with appropriate informative content. The overall objective is to develop a website inspired by popular social networks such as Facebook, Twitter, and the former Orkut, providing an accessible space where the target audience can easily and effectively seek professional help. The methodology adopted is based on the Spiral Model, which combines prevention and tolerance to changes. This model assumes that changes are the results of project risks and includes explicit risk management activities to reduce them. Drawing on concepts from Design Science Research (DSR), an adaptation was generated to provide a more structured approach to the development of the social network. The obtained results demonstrated the positive acceptance of the social network through the validation of the developed software using a focus group and Likert scale questions. The website interface was considered simple and intuitive, conveying a sense of security and trust to users. Additionally, the implemented forum on the platform proved to be a viable solution, allowing users to share their experiences and find emotional support. All participants in the focus group would recommend the social network to others. It was concluded that there is a significant gap in the market for social networks targeting the LGBTQ+ community, with the majority of current applications and platforms predominantly focused on dating and relationships, neglecting the need for a dedicated space for support and freedom of expression. The implementation of the forum in Desabafa Aí proved to be a viable solution, but there is still much to be done to fully meet the needs of this diverse audience.
Keywords: Rede social; Minorias; Apoio Emocional; Discurso de ódio; Modelo Espiral; Grupo focal; Social Media; Minorities; Emotional Support; Hate Speech; Spiral Model; Focus Group; CNPQ::ENGENHARIAS